The relationship between student funding policy and academic achievement of management students in Enade - Marcio Eduardo Garcia Bezerra; Monica Mota Tassigny (Arizona State University, 2018)
Fies and ProUni students financing programs intensified the access to higher education and mobilized the creation of courses, with the management course as one of the most favored. However, few studies have discussed the aspects of this policy to foment higher education influencing students' academic performance. In this way, this article aim to measure, through the method of the binary choice dependent models (Probit model), the probability that the management students participating in the financing programs will achieve a good academic performance in Enade 2015. Based on the results, it was concluded that these student funding programs positively and significantly influenced the likelihood of students achieving above-average academic performance of management students. The costing modalities of management students associated with ProUni had the highest probabilities of a positive effect on performance, while Fies, although positive, had a marginal probabilistic marginal effect in relation to academic performance.